Mucocele-like lesions of the breast: a long-term follow-up study - Hatanaka Kazuhito; Yoshioka Takako; Sagara Yoshiaki; Kukita Taeko; Tamada Shugo; Baba Shinichi; Sagara Yasuaki; Rai Yoshiaki; Umekita Yoshihisa; Ohi Yasuyo; Sagara Yoshiatsu; Tanimoto Akihide (BMC, 2011)
Abstract Background Mucocele-like lesions (MLL) of the breast were originally described as benign lesions composed of multiple cysts lined by uniform flat to cuboidal epithelium with extravasated mucin, but subsequent reports described the coexistence of columnar cell lesions (CCL), atypical ductal hyperplasia (ADH) and ductal carcinoma in situ (DCIS). Several reports have investigated whether core biopsy can diagnose MLL reliably; however, there is only one report with a long-term follow-up after excision of MLL. We report here 15 surgically excised MLL with a long-term follow-up. Findings Fifteen lesions diagnosed as MLL from 13 patients who had undergone excisional biopsy between January 2001 and December 2006 were retrieved and followed-up for 24-99 months (median 63.8). Two lesions were accompanied with CCL, 5 with ADH and 3 with low grade DCIS. Four lesions (2 ADH, 2 DCIS) were additionally resected and their histology revealed 2 ADH, one DCIS and one MLL with CCL. Of 4 lesions (3 ADH, one DCIS) without additional resection, one lesion (ADH) relapsed accompanied with DCIS at 37 months after excision. Conclusions MLL were frequently accompanied with CCL, ADH or low grade DCIS. Complete resection may be recommended in case of MLL with ADH or DCIS because of intralesional heterogeneity and the probabilities of relapse.